1970
DOI: 10.3126/hren.v8i2.4420
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Fatal Head Injury in Road Traffic Accident Cases: A Study from BPKIHS, Dharan

Abstract: Setting: Study was performed in mortuary of B P Koirala Institute of Health Sciences (BPKIHS), Dharan. Objectives: 1. To know the various epidemiological factors related to road traffic accident cases. 2. To know the relationship of head injury in road traffic accidents with the factors like helmet use, type of vehicle involved in accident. Study design: longitudinal descriptive study. Study unit: 77 Dead bodies with fatal head injury from RTA coming to BPKIHS mortuary, a focal point in eastern Nepal Study var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
61
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 10 publications
17
61
2
Order By: Relevance
“…But in contrast, one of the study from India illustrated that majority of RTA cases were graduates followed by intermediate education [24]. Our findings revealed RTAs occurred higher in public holiday and previous study from India highlighted similar findings [17]. It could be the higher proportion of the people's movement for marketing and outing on holiday.…”
Section: Discussioncontrasting
confidence: 32%
See 1 more Smart Citation
“…But in contrast, one of the study from India illustrated that majority of RTA cases were graduates followed by intermediate education [24]. Our findings revealed RTAs occurred higher in public holiday and previous study from India highlighted similar findings [17]. It could be the higher proportion of the people's movement for marketing and outing on holiday.…”
Section: Discussioncontrasting
confidence: 32%
“…The frequently vulnerable groups of RTAs are pedestrians [16], motorcyclists, bicyclists, scooter riders, children and elderly people. The most of the accidents are unnatural and easily preventable [15], in which vehicle condition and environmental factors are accountable to the RTAs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Male preponderance with 6.4:1 was also expected and is in line with worldwide trends [10][11][12][13][14][15][16][17] .This trend of male to female ratio depends on the role of females in society.…”
Section: Distribution Of Patients According To Literacy Discussionsupporting
confidence: 50%
“…5 pme8.59 pm was the peak hour reflected in another study conducted in Mangalore. 15 In another study conducted by Jha in Pondicherry, 16 the peak time observed was between 4e5 pm and 6e7 pm. The slight difference in timings as compared to our study can be due to difference in work culture (and hence peak hours) of the two cities.…”
Section: Discussionmentioning
confidence: 92%